Tissue Engineering for the Insertions of Tendons and Ligaments: An Overview of Electrospun Biomaterials and Structures - Sensini, Alberto; Massafra, Gabriele; Gotti, Carlo; Zucchelli, Andrea; Cristofolini, Luca (Frontiers in Bioengineering and Biotechnology, 2021)
The musculoskeletal system is composed by hard and soft tissue. These tissues are characterized by a wide range of mechanical properties that cause a progressive transition from one to the other. These material gradients are mandatory to reduce stress concentrations at the junction site. Nature have answered to this topic developing optimized interfaces, which enable a physiological transmission of load in a wide area over the junction. The interfaces connecting tendons and ligaments to bones are called entheses, while the ones between tendons and muscles are named myotendinous junctions. Several injuries can affect muscles, bones, tendons or ligaments and they often occur at the junction sites. For this reason, the main aim of the innovative field of the interfacial tissue engineering is to produce scaffolds with biomaterial gradients and mechanical properties to guide the cell growth and differentiation. Among the several strategies explored to mimic these tissues, the electrospinning technique is one of the most promising, allowing to generate polymeric nanofibers similar to the musculoskeletal extracellular matrix. Thanks to its extreme versatility, electrospinning has allowed the production of sophisticated scaffolds suitable for the regeneration of both the entheses and the myotendinous junctions. The aim of this review is to analyze the most relevant studies that applied electrospinning to produce scaffolds for the regeneration of the enthesis and the myotendinous junction, giving a comprehensive overview on the progress made in the field. In particular focusing on the electrospinning strategies to produce these scaffolds and their mechanical, in vitro and in vivo outcomes.